Development of metformin HCl granules using brown flaxseed mucilage as a retardant polymer: effects of polymer and drug ratio - Lucas Oliveira Rodrigues; Deborah Quintanilha Falcão; Samanta Cardozo Mourão (Universidade de São Paulo, 2023)
Abstract Flaxseed (Linum usitatissimum L.) is the seed of a multipurpose plant of pharmaceutical interest, as its mucilage can be used as a natural matrix to develop extended-release dosage forms and potentially replace synthetic polymers. In this study, a 3² factorial design with two replicates of the central point was applied to optimize the development of extended-release granules of metformin HCl. The total fiber content of the mucilage as well as the friability and dissolution of the formulations were evaluated. The lyophilized mucilage presented a high total fiber content (42.63%), which suggests a high efficiency extraction process. Higher concentrations of the mucilage and metformin HCl yielded less friable granules. In addition, lower concentrations of metformin HCl and higher concentrations of the mucilage resulted in slower drug release during the dissolution assays. The release kinetics for most formulations were better represented by the Hixson-Crowell model, while formulations containing a higher concentration of the mucilage were represented by the Korsmeyer-Peppas model. Nonetheless, five formulations showed a longer release than the reference HPMC formulation. More desirable results were obtained with a higher concentration of the mucilage (13-18%) and a lower concentration of metformin (40%).